Theoretical Research and Numerical Simulation on Water Resistance Mechanism of Textile Bag in Water Passage. (8th March 2021) - Li, Ang; Yang, Yuxuan; Zhu, Mingcheng; Zhang, Wenzhong; Ji, Bingnan; Ding, Xuesong
Abstract : It is an important problem in the mine water disaster prevention and control to control the large passage moving water. Traditional grouting technology is to put coarse aggregate and fine aggregate downward first and then grouting treatment. But the aggregate and cement flow distance is long, consumption is large, cost is high, and easy to appear secondary water inrush. Centering on the technical difficulties in the rapid construction of the blocking body of the moving water passage, a water-blocking textile bag was invented. The purpose of blocking the tunnel water inrush was achieved by grouting inside the bag body, which fundamentally realized the rapid blocking of the large passage through water under the condition of moving water. However, the mechanism, water plugging law, and design parameters of water blocking roadway with textile bag are still unclear. In this paper, the slip law and stability of the textile bag in the moving water and the deformation characteristics caused by the dynamic water pressure are theoretically analyzed and simulated. Through theoretical analysis, the ultimate antihydraulic stress value of a textile bag of a certain specification is calculated, and the parameters of the textile bag that affect the stability of the bag body are also determined. Xflow was used for numerical simulation analysis to study the deformation characteristics of the textile bag under water and the law of water barrier. The simulation analysis focuses on the water resistance effect and flow field distribution characteristics of the textile bag in the water passage under the condition of low flow rate and low pressure, as well as the stability and self-deformation characteristics of the textile bag under the condition of high flow rate and high pressure. The accuracy of the limit resistance to water pressure of the textile bag obtained from theoretical analysis is verified. The results show that the theoretical analysis is consistent with the simulation results. The textile bag can realize the fast controllable plugging of the large water passage of moving water within the limit of the antihydraulic stress.